The Influence of Experiential Marketing and Service Quality on Customer Loyalty Through Customer Satisfaction (A Study On PT Bank Rakyat Indonesia (Persero) Tbk Bandar Jaya Office Branch) - Pramesti, Revianita Sekar Asri; Wardhianto, K Bagus (Jurnal Kompetitif Bisnis, 2022)
This study aims to determine how the effectt of experiential marketing and service quality on customer loyalty through satisfaction. The research method used is explanatory research technique with a quantitative approach, the research was conducted at PT Bank Rakyat Indonesia (Persero) Tbk Bandar Jaya Branch Office. Data was collected using a questionnaire with a total sample of 100 respondents, data analysis techniques used descriptive analysis techniques and statistical analysis using SmartPLS. The results show that experiential marketing can significantly affect customer satisfaction, experiential marketing can significantly affect customer loyalty, service quality can significantly affect customer satisfaction, service quality cannot significantly affect customer loyalty, customer satisfaction can significantly affect customer loyalty, customer satisfaction variable acts as a mediating variable between experiential marketing variables on customer loyalty partially and service quality variables on full customer loyalty.